Ignasi Casanovas and Frederic Clascar. Historiography and rediscovery of the thought of the 1700s and 1800s - Batllori, Miquel (Journal of Catalan Intellectual History, 2011)
This text shows the similitudes and the differences between Ignasi Casanovas and Frederic Clascar, two of the most important representatives of the religious thought in Catalonia, in the first third of the 20th century. The article studies their philosophical writings in the rich context of their global work, analysing their deficiencies and underlining the positive contribution to the Catalan culture. key words Ignasi Casanovas, Frederic Clascar, religious thought.